The Polarity-Specific Nature of Single-Session High-definition Transcranial Direct Current Stimulation to the Cerebellum and Prefrontal Cortex on Motor and Non-motor Task Performance - Maldonado, Ted; Bernard, Jessica A. (Cerebellum (London, England), 2021)
The cerebellum has an increasingly recognized role in higher order cognition. Advancements in noninvasive neuromodulation techniques allow one to focally create functional alterations in the cerebellum to investigate its role in cognitive functions. To this point, work in this area has been mixed, in part due to varying methodologies for stimulation, and it is unclear whether or not transcranial direct current stimulation (tDCS) effects on the cerebellum are task or load dependent. Here, we employed a between-subjects design using a high definition tDCS system to apply anodal, cathodal, or sham stimulation to the cerebellum or prefrontal cortex (PFC) to examine the role the cerebellum plays in verbal working memory, inhibition, motor learning, and balance performance, and how this interaction might interact with the cortex (i.e., PFC). We predicted performance decrements following anodal stimulation and performance increases following cathodal stimulation, compared with sham. Broadly, our work provides evidence for cerebellar contributions to cognitive processing, particularly in verbal working memory and sequence learning. Additionally, we found the effect of stimulation might be load specific, particularly when applied to the cerebellum. Critically, anodal stimulation negatively impacted performance during effortful processing, but was helpful during less effortful processing. Cathodal stimulation hindered task performance, regardless of simulation region. The current results suggest an effect of stimulation on cognition, perhaps suggesting that the cerebellum is more critical when processing is less effortful but becomes less involved under higher load when processing is more prefrontally dependent.